2020
DOI: 10.5937/ekopolj2002359m
|View full text |Cite
|
Sign up to set email alerts
|

The impact of customer contact as part of the agricultural products distribution channel on the increase of the competitiveness of agricultural holdings

Abstract: The main objective of this paper stems from the need to provide new insights into the competitiveness of the agricultural products distribution system in the Republic of Serbia, through determining the impact of customer contact as part of the agricultural distribution channel on the competitiveness of agricultural holdings. The survey was conducted on a sample of 126 farms from the territory of the Republic of Serbia through a closed-type survey (12 claims related to customer contact and 15 claims related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Naturally, people contribute to more complete usage of some natural potentials, so the benefits are used for the development of various types of tourism. For example wine tourism, which is extensively researched in the scientific and professional literature (Anđelić et al, 2019), organic production, as well as rural tourism, and closely observed agritourism as an addition to the existing types of contacts with clients and agricultural product distribution already discussed by Milanovic et al (2019) and Milanović et al (2020).…”
Section: Introductionmentioning
confidence: 95%
“…Naturally, people contribute to more complete usage of some natural potentials, so the benefits are used for the development of various types of tourism. For example wine tourism, which is extensively researched in the scientific and professional literature (Anđelić et al, 2019), organic production, as well as rural tourism, and closely observed agritourism as an addition to the existing types of contacts with clients and agricultural product distribution already discussed by Milanovic et al (2019) and Milanović et al (2020).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, the resilience and competitiveness of agriculture could be increased if it is taken into consideration the degree of predictability of what happens with the crops during the agricultural year: production/hectare, cost, price, and processing costs. In a different study, it is claimed that competitiveness represents the situation in which an economic sector competes with other economic sectors (Milanović, Nikitović, and Garabinović, 2020). Thus, competitiveness in the agriculture sector is influenced by technological advancements, production costs and selling prices, changes in the demand, and environmental issues.…”
Section: Review Of the Scientific Literaturementioning
confidence: 99%
“…To achieve a competitive advantage, the entrepreneur organization must establish an adequate level of planning, implementation, and evaluation of training and development programs for employees (Tošović-Stevanović & Bogdanović, 2018). Competitiveness is an indicator of the position that an analyzed entity occupies in a particular market, its ability to cope with direct or indirect competitors in the right way, but also a key source of creating opportunities for business improvement and long-term success (Milanovic, Nikitovic & Garabinovic, 2020). Competitive advantage can be defined as a unique position that a company develops in comparison to its competition (Markovic, Salamzadeh & Vujicic,2019).…”
Section: Employee Development Process Management As An Aspect Of Comp...mentioning
confidence: 99%